2023
DOI: 10.1111/2041-210x.14188
|View full text |Cite
|
Sign up to set email alerts
|

New data‐driven method for estimation of net ecosystem carbon exchange at meteorological stations effectively increases the global carbon flux data

Abstract: The eddy covariance (EC) flux stations have great limitations in the evaluation of the global net ecosystem carbon exchange (NEE) and in the uncertainty reduction due to their sparse and uneven distribution and spatial representation. If the EC stations are linked with widely distributed meteorological stations using machine learning (ML) and remote sensing, it will play a big role in effectively improving the accuracy of the global NEE assessment and reducing uncertainty. In this study, we developed a framew… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 46 publications
0
1
0
Order By: Relevance
“…The RF model is considered a reasonable and suitable method for simulating CO 2 fluxes from site to regional scales. Firstly, as a machine learning algorithm, the RF model selects the optimal output from multiple regression trees to capture the features of the data, effectively enhancing the accuracy of flux data [56,57]. Secondly, by extracting the multivariate functional relationships between observed data and explanatory variables, the RF model can integrate data from different sources and simplify complex processes, addressing nonlinear issues in ecosystems [58].…”
Section: Discussionmentioning
confidence: 99%
“…The RF model is considered a reasonable and suitable method for simulating CO 2 fluxes from site to regional scales. Firstly, as a machine learning algorithm, the RF model selects the optimal output from multiple regression trees to capture the features of the data, effectively enhancing the accuracy of flux data [56,57]. Secondly, by extracting the multivariate functional relationships between observed data and explanatory variables, the RF model can integrate data from different sources and simplify complex processes, addressing nonlinear issues in ecosystems [58].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in ecological dynamics of net ecosystem exchange (NEE), Kong et al (2022) expressed that NEE's interactions with other environmental variables remained a challenging task for the reasons that the latter varies across ecosystems and climate regimes. In Zhang et al (2023), the inclusion of NEE was observed to improve the terrestrial photosynthesis model and global carbon cycle prediction amidst climate changes. The same assertion was shown by Mahmud et al (2021) for dryland global carbon cycle contribution using the global terrestrial biosphere model including those predicted for urban forests 22,23 , peatland mosses 24 , tropical vegetation 25 , as well as environmental processes of soil respirations ?,27 and land-ocean-atmosphere carbon exchange 28,29,30 .…”
Section: Introductionmentioning
confidence: 99%